CARMN Loss Regulates Smooth Muscle Cells and Accelerates Atherosclerosis in Mice. Issue 9 (30th April 2021) - Vacante, Francesca; Rodor, Julie; Lalwani, Mukesh K.; Mahmoud, Amira D.; Bennett, Matthew; De Pace, Azzurra L.; Miller, Eileen; Van Kuijk, Kim; de Bruijn, Jenny; Gijbels, Marion; Williams, Thomas C.; Clark, Michael B.; et al.
Abstract : Rationale: In the microenvironment of atherosclerotic lesions, vascular smooth muscle cells (vSMCs) switch to a dedifferentiated state but the underlying molecular mechanisms driving this switch are not fully understood. Long noncoding RNAs (lncRNAs) are dysregulated during vascular pathology, but relatively little is known about their involvement in controlling vSMCs function. Cardiac mesoderm enhancer-associated noncoding RNA (CARMN) is a lncRNA located immediately upstream of the microRNAs-143 and -145 (miR-143 and miR-145 ), both involved in vSMCs function. Objective: We investigated the role of the lncRNA CARMN, independent from miR-143 and miR-145, as a potential regulator of vSMC phenotypes in vitro and the consequences of its loss during the development of atherosclerosis in vivo. We hypothesized that loss of CARMN is a primary event controlling the functional switch towards proatherogenic vSMC phenotype and accelerates the development of the plaques in vivo. Method and Results: Expression of CARMN lncRNA was silenced using locked nucleic acids antisense oligonucleotides (GapmeRs) in human coronary arterial smooth muscle cells, revealing that GapmeR-mediated loss of CARMN negatively affects miR-143 and miR-145 microRNA expression. RNA sequencing of CARMN-depleted human coronary arterial smooth muscle cells revealed large transcriptomic changes, associated with vSMC proliferation, migration, inflammation, lipid metabolism, and dedifferentiation. The use of miR-143 and miR-145 mimics revealed that CARMN regulates human coronary arterial smooth muscle cell proliferation in a microRNA-independent manner. In humans and mice, CARMN and associated microRNAs were downregulated in advanced versus early atherosclerotic lesions. Using a CRISPR (clustered regularly interspaced short palindromic repeats)-Cas9 (CRISPR-associated protein 9) knockout approach, we explored the implications of CARMN depletion during atherosclerosis in vivo. Consistent with in vitro results, the knockout of CARMN impaired the expression of miR-143 and miR-145 under homeostatic conditions. Importantly, when atherosclerosis was induced in these mice, CARMN knockout increased the volume, size, proinflammatory Lgals3 (galectin 3)-expressing cells content, and altered plaque composition, yielding an advanced phenotype. Conclusions: We identified the early loss of CARMN lncRNA as critical event which primes vSMCs towards a proatherogenic phenotype in vitro and accelerates the development of atherosclerosis in vivo. Abstract : Supplemental Digital Content is available in the text.